PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Afandi, Cicanthika Dyah Fitria; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the influence of Intellectual Capital which is proxy by Pulic model (VAIC) and company performance which is proxy by Return on Equity (ROE) in the LQ-45 companies which are listed in Indonesia Stock Exchange. The sample in this research is the LQ-45 companies which are listed in Indonesia Stock Exchange (IDX). In this research the sample collection technique has been done by using purposive sampling, and based on the predetermined criteria, then 17 samples LQ-45 companies in 2013-2015 periods have been selected. This research has been carried out by using multiple linear regression analysis and SPSS version 23. The result of the research shows that: (1) value added capital employed (VACA) give positive influence to the Return On Equity (ROE); (2) value added human capital (VAHU) does not give any influence to the Return On Equity (ROE); (3) structural capital (STVA) does not give any influence to the Return On Equity (ROE).Keywords: intellectual capital, return on equity, value added capital employed, value added human capital, structural capital value added